Happiness and Religion - Jan Fidrmuc; Cigdem Börke Tunali (Center for Economic Studies and ifo Institute (CESifo), 2015)
We use four ways of the European Social Survey, covering 2000 to 2008, to analyze the effect of religion on happiness. Our findings confirm that religious individuals are generally happier than non-religious ones. When we seek to disentangle the effects of belonging to an organized religion from the effect of holding religious beliefs, we find that the former lowers happiness while the latter raises it. We interpret this as evidence that the tangible aspects of religion (such as abiding by restrictions on consumption and behavior) decrease happiness while the spiritual aspects increase it. We also find important differences among members of different religious denominations, and between men and women, with females more adversely affected by the tangible aspects of belonging to a religion.
Keywords: I31; Z12; 330; religion; happiness